The Role of the Neutrophil-to-Lymphocyte Ratio in the Development of Heart Failure in Patients with Concomitant Hypertension, Type 2 Diabetes, and Obesity - Shelest, Borys; Babycheva, Oleksandra; Sadovenko, Olga; Kalmykov, Oleksii; Rodionova, Iulia; Sukhonos, Nataliia; Kovalova, Yuliia; Shelest, Oleksiy (Medicinski časopis, 2025)
Objective. Arterial hypertension, type 2 diabetes mellitus (T2DM), and obesity increase cardiovascular risk, including heart failure (HF). The neutrophil-to-lymphocyte ratio (NLR), a systemic inflammation marker, has been linked to adverse cardiovascular outcomes, but its role in HF development remains unclear. This study evaluated NLR as a predictor of HF in these patients. Methods. A total of 293 patients with essential hypertension, T2DM, and obesity were enrolled in a prospective study. They were categorized into two groups: HF group (n=85) and non-HF group (n=208). NLR was calculated from complete blood count results. HF was diagnosed based on the 2023 ESC guidelines and confirmed via biomarkers (NT-proBNP) or echocardiography. Patients were followed for 24 months. Results. Patients who developed HF had significantly higher NLR (3.39 ± 1.23 vs. 2.66 ± 1.14, p<0.001). HF patients also had longer T2DM (12.75 ± 5.86 vs. 10.25 ± 4.39 years, p<0.001) and hypertension durations (18.87 ± 8.54 vs. 16.05 ± 7.14 years, p=0.004). A non-dipper blood pressure profile was more frequent in the HF group (36.5% vs. 20.7%, p=0.005). In multivariate regression, NLR (OR 1.383; 95% CI 1.073–2.222; p=0.037), non-dipper BP profile, and disease duration remained independent HF predictors. Conclusion. NLR is independently associated with HF onset in patients with hypertension, T2DM, and obesity. It may serve as a simple, cost-effective biomarker for HF risk stratification, facilitating early intervention and improved outcomes.